Proyek Flipchart Solusi Meningkatkan Kreativitas Siswa Dalam Pembelajaran Sejarah - Shanti Fatiarif Zashiyah Aly; Wawan Darmawan (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2022)
The spread of the Covid-19 virus has had an impact on various aspects of life, including the world of education. Require each government to implement emergency policies to reduce and stop the Covid-19 virus pandemic. In Indonesia, in the field of education, distance learning policies are issued or carried out online at home for each school. Learning that is carried out online is no exception at MAN 2 Sukabumi City and is a new thing that is also a challenge for every school. These challenges then have an impact on the process and learning outcomes carried out by teachers and students. The learning problem that is seen and becomes a concern during the online history learning process, especially in class X IPS 4 MAN 2 Sukabumi City is the low creativity of students which is included in 21st century skills. There are several indicators of creativity that are low and lacking in students. The current conditions with the implementation of online learning, although recently limited face-to-face meetings have begun, make it necessary to use an online platform to support the learning process and conduct research during this pandemic. Based on these problems, the formulation of the problems taken in this research is how to increase students' creativity in learning history through the application of flipchart projects with the help of the Whast App application. The method used in this research is a classroom action research (CAR) method using a design developed by Ebbut. Based on the research results, the application of flipchart projects can be a solution to increase students' creativity in learning history. Keywords: flipchart, 21st century skills, creativity, project-based learning, history learning, classroom action research (car)